MODEL PERUBAHAN DAN PENGEMBANGAN ORGANISASI PERUSAHAAN DI INDONESIA - FX Supriyono (Center for Economic Studies Universitas Katolik Parahyangan, 2005)
This paper is about organizational change. The dynamic of the environment fade today creates many' changes that must be faced by all organizations around the world. The liberation of economic system; the advancement of information technology; competition; and demographics changes will forced the organization, to change the system that already established. However, the process oi change need a great effort, time and energy to Tight against the power of the status quo.To respond the changes in the environment, the organizations should do the development programs, (OD Program) that is the planned system wide effort managed from the top with the assistance of a change agents to, improve the organization, effectiveness. Without an effective, OD program, organizations will collapse in the competitions.Keywords: Organization change; liberation of the economic; system; and organizational development.